The Use of Social Media in Public Services Delivery: A Case in Selected West Java Local Governments - Amiruddin Setiawan (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
Adoption of social media by government agencies is typically associated with the promotion of transparency, participation, and cooperation. However, less emphasis has been placed on the use of social media for public service delivery. As a result, this article investigates the tactics used by eight local governments in West Java Province to develop content for social media. To that end, the research re-creates a well-known interpretive framework of social media interactions in the public sector, focusing on three categories: information provision, citizen involvement, and public service delivery. The present research puts the methodology to the test by analyzing Twitter data from a key collection of local governments. The findings support the use of social media to disseminate institutional information and encourage connections with people. At the same time, local governments in West Java  are beginning to employ social media to perform public services.